A new species of Acanthochondria Oakley, 1927 (Copepoda: Chondracanthidae) parasitizing the flounder Xystreurys rasile (Pleuronectiformes: Paralichthyidae) from Argentina - Alarcos, Ana Julia (2011)
A new copepod species, Acanthochondria sagitta sp. n., is described based on specimens collected from the flounder Xystreurys rasile (Jordan) (Pleuronectiformes, Paralichthyidae), caught in the coastal waters off Necochea, Buenos Aires Province, Argentina. The new species differs from its congeners by the following combination of characters: presence of three pairs of cephalic outgrowths; the triangular shape of the trunk with diverging postero-lateral processes; leg 2 of an intermediate shape between Types C and D, which projects laterally from the trunk, and Type B-V antennule bearing two proximal processes (one ventral and one dorsal) on the swollen basal portion.